2015
DOI: 10.4103/0970-9371.171222
|View full text |Cite
|
Sign up to set email alerts
|

Bax and Bak expression in cervical smears of women with low-and high-risk HPV types: A study of 120 cases

Abstract: Background:Human papillomavirus (HPV) is known to be involved in the carcinogenesis of squamous cells in uterine cervix cancer, mostly by binding and inactivating the p53 and pRb tumor suppressor genes. Lately, evidence has emerged suggesting that HPV oncoproteins may interact with proteins involved in cellular apoptosis as well.Aim:This study aimed to investigate the expression of proapoptotic proteins Bax and Bak in women with low-risk and high-risk HPV types as opposed to HPV-negative women, and in women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In 2015, an Indian group performed the HPV test, cytology test, and Bax/Bak staining in 120 specimens of cervical liquid-based cytology samples and found that Bax/Bak staining was only weakly correlated with cytological results, although these negative results may be attributable to the small sample size. Moreover, in all cases, the results showed that there is no statistically significant difference in the Bax and Bak scores between any compared groups including the control, low-risk HPV types, and high-risk HPV types group 51. Therefore, the Bax/Bak may not be considered as an accurate immunocytochemistry biomarker for cervical cancer screening according to the existing data.…”
Section: Exploration Of Other Cytological Markersmentioning
confidence: 86%
“…In 2015, an Indian group performed the HPV test, cytology test, and Bax/Bak staining in 120 specimens of cervical liquid-based cytology samples and found that Bax/Bak staining was only weakly correlated with cytological results, although these negative results may be attributable to the small sample size. Moreover, in all cases, the results showed that there is no statistically significant difference in the Bax and Bak scores between any compared groups including the control, low-risk HPV types, and high-risk HPV types group 51. Therefore, the Bax/Bak may not be considered as an accurate immunocytochemistry biomarker for cervical cancer screening according to the existing data.…”
Section: Exploration Of Other Cytological Markersmentioning
confidence: 86%
“…The pro-apoptotic proteins Bax and Bcl-2 can cause liberation of cytochrome C (Liu et al 2008;Noguchi et al 1999). In apoptosis process, overexpression of Bcl-2 can enhance the process by blocking Bax (Klapsinou et al 2015). Death receptor apoptosis and mitochondrial apoptosis are the two important apoptosis pathways (Su et al 2016;Lu et al 2017a, b).…”
Section: Mir-466c-3p Over-expression Inhibits the Mitochondrial Apoptmentioning
confidence: 99%
“…In the process of apoptosis, the overexpression of Bax may encourage apoptosis via blocking Bcl-2, which is an antiapoptotic protein [ 30 ]. It had been reported earlier that both the death receptor and the mitochondrial apoptosis pathway (MAP) are the important pathways [ 31 , 32 ]. Bax is an important regulator in the MAP, and the molecule is able to build up homodimers on the mitochondrial membranes and lead to the opening of permeability pores on it for releasing CYT- C from the mitochondria in the cytoplasm [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the process of apoptosis, the overexpression of Bax may encourage apoptosis via blocking Bcl-2, which is an antiapoptotic protein [30]. It had been reported earlier that both the death receptor and the mitochondrial apoptosis pathway (MAP) are the important pathways [31,32].…”
Section: Upregualtion Of Mir-142-3p Inhibits the Mitochondrial Apoptomentioning
confidence: 99%